Coronary vasospasm as the underlying cause for chest pain in patients with PVB19 myocarditis. Issue 11 (29th January 2008) - Yilmaz, A; Mahrholdt, H; Athanasiadis, A; Vogelsberg, H; Meinhardt, G; Voehringer, M; Kispert, E-M; Deluigi, C; Baccouche, H; Spodarev, E; Klingel, K; Kandolf, R; et al.
Abstract : Objective: To evaluate the incidence of coronary vasospasm as a possible pathophysiological mechanism causing chest pain symptoms in patients with clinically suspected myocarditis. Design and setting: Prospective study in a teaching hospital. Patients: 85 patients who presented at hospital with atypical chest pain and demonstrated clinical signs suggestive of myocarditis. Main outcome measures: Incidence of coronary vasospasm demonstrated by intracoronary acetylcholine (ACh) testing. Methods: The combined procedure of intracoronary ACh testing and endomyocardial biopsy (EMB) was performed after ruling out significant coronary artery disease (CAD). EMBs were analysed for myocardial inflammation by immunohistological methods and for virus genome persistence. Results: Pathological biopsy results, including myocardial inflammation or detection of viral genomes, or both, were found in 55 (64.7%) patients while 30 (35.3%) patients showed neither cardiac inflammation nor viral genomes and were defined as the control group. Coronary vasospasm was demonstrated in 39/55 (70.9%) patients with pathological results compared with only 12/30 (40.0%) with normal biopsy results (p = 0.01). Patients with isolated PVB19 infection (n = 22) demonstrated a significantly higher incidence of coronary vasospasm than both those with isolated HHV6 infection (86.4% vs 46.7%; p = 0.025) and those with normal biopsy results (86.4% vs 40.0%; p<0.001). Univariate and multivariate logistic regression analysis showed that only PVB19 infection was independently correlated with coronary vasospasm (OR = 4.9, 95% CI 1.56 to 15.28, p = 0.006). Conclusions: Coronary vasospasm is one of the main reasons for atypical chest pain in patients with clinical signs of myocarditis and biopsy-proven PVB19 myocarditis in the absence of significant CAD.